Dose requirements for idarucizumab reversal of dabigatran in a lethal porcine trauma model with continuous bleeding - Honickel, Markus; Spronk, Henri M.; Rossaint, Rolf; Stoppe, Christian; van Ryn, Joanne; ten Cate, Hugo; Grottke, Oliver (Thrombosis and Haemostasis, 2017)
Idarucizumab is licensed for emergency reversal of dabigatran. A single 5 g dose is usually sufficient, but higher doses may sometimes be required and optimum dosing has not been defined. It was the aim of this study to investigate the effect of idarucizumab, given once or as a split dose, after double trauma in pigs anticoagulated with dabigatran. Dabigatran etexilate (30 mg/kg bid) was given to 18 male pigs orally for 3 days. On day 4, animals were randomised 1:1:1 to receive idarucizumab 60+0, 60+60 or 120+0 mg/kg. Doses were administered 15 and 75 minutes after initial liver trauma. At 60 minutes, a second liver injury was undertaken. Animals were monitored for 5 hours after initial trauma or until death. Blood loss during the first hour was 990 ± 109 ml, 988 ± 84 ml and 964 ± 75 ml in the 60+0, 60+60 and 120+0 groups, respectively. In the 120+0 and 60+60 groups, total blood loss was 1659 ± 346 and 1426 ± 106 ml, respectively, and survival at 5 hours was 100 %. However, in the 60+0 group, total blood loss was 3561 ± 770 ml and survival was 50 %. Analysis of dabigatran plasma concentrations showed that equimolar concentrations of idarucizumab are necessary to bind all dabigatran and achieve sufficient thrombin generation. At sufficient doses, idarucizumab rapidly reduced blood loss and improved survival in this lethal porcine model of double trauma with dabigatran anticoagulation. In clinical practice, should bleeding continue after initial treatment with the approved 5 g dose of idarucizumab, a second dose may potentially be effective to control bleeding caused by redistribution of unbound dabigatran.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Anticoagulants; antidote; dabigatran; idarucizumab; trauma